2009
DOI: 10.1111/j.1365-2702.2009.02896.x
|View full text |Cite
|
Sign up to set email alerts
|

Translation and back‐translation in qualitative nursing research: methodological review

Abstract: Development of the translation procedures could provide qualitative nursing researchers with a guide when collecting data in one language and presenting results in another language. In this way, the necessary rigour in qualitative nursing research could be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
290
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(298 citation statements)
references
References 21 publications
1
290
1
6
Order By: Relevance
“…Validity was ensured by checking back transcripts against original audio recordings for accuracy, thereby confirming the semantic equivalence of the data. [15] The transcripts were prepared for coding by providing adequate space at the margin for comments. Using highlighters, potential patterns were marked as follows: (i) notes on the text were analysed with highlights; (ii) codes were identified and matched with extracted data; (iii) codes were collated together on a board; (iv) the different codes were sorted into potential themes, grouping relevant coded data extracted within the identified themes in tabular form with names of code and the meaning identified and described; (v) using an iterative process, a thematic map was generated from the FGD and in-depth interview sessions; (vi) themes were defined and redefined; the themes involved identifying what was important in answering the research questions.…”
Section: Discussionmentioning
confidence: 99%
“…Validity was ensured by checking back transcripts against original audio recordings for accuracy, thereby confirming the semantic equivalence of the data. [15] The transcripts were prepared for coding by providing adequate space at the margin for comments. Using highlighters, potential patterns were marked as follows: (i) notes on the text were analysed with highlights; (ii) codes were identified and matched with extracted data; (iii) codes were collated together on a board; (iv) the different codes were sorted into potential themes, grouping relevant coded data extracted within the identified themes in tabular form with names of code and the meaning identified and described; (v) using an iterative process, a thematic map was generated from the FGD and in-depth interview sessions; (vi) themes were defined and redefined; the themes involved identifying what was important in answering the research questions.…”
Section: Discussionmentioning
confidence: 99%
“…Where standardized assessment tools are used, there is guidance to ensure that translation is accurate and reliable with several stages of forward and back translation and validation of each step. 19 There is no guidance for using translated patient interviews as an outcome measure. We have shown that the reliability of the mRS as an outcome measure is maintained when scoring translated assessments from 2 culturally diverse populations.…”
Section: Translation Substudymentioning
confidence: 99%
“…back-translation (Coolican, 2009), jakožto jedna z nejpoužívanějších metod překladu výzkumných nástrojů (Chen & Boore, 2009). …”
Section: Metoda Výzkumuunclassified